(untitled) (Research, Society and Development, 2022)
Croton blachetianus, popularly called marmeleiro, is a shrub rich in secondary metabolites that has several biological activities. The aim of this study was to determine the composition of volatile compounds in the essential oil of dry leaves of C. blanchetianus and its antimicrobial action (minimum inhibitory dose – vapor DMI) on lactic acid bacteria (LAB), Weissella viridescens and Leuconostoc mesenteroides, spoilage bacteria for meat products. The essential oil from the dry leaves of C. blanchetianus was extracted by the hydrodistillation technique and the volatile compounds were analyzed by CG headspace technique. The minimum inhibitory dose in the vapor phase was defined as the minimum dose of an essential oil solution of C. blanchetianus in 5% DMSO whose vapor completely inhibits BAL’s growth for 48 hours. Subsequently, the bactericidal and bacteriostatic effect was determined. The major compounds found were eucalyptol (32.94%) and D-α-Pinene (29.43%) terpenes. The minimum inhibitory dose was 0.32g/mL for both microorganisms. The bactericidal effect for W. viridescens was observed by the action of vapor from the 0.32 g/mL solution and for L. mesenteroides the bacteriostatic and bactericidal effect was observed by the action of vapor from the 0.40 g/mL and 0.57 solution g/ml, respectively. Thus, it was possible to observe the presence of terpenes, as major compounds in the headspace analysis, as well as the antimicrobial, bacteriostatic and bactericidal activity of the essential oil from dry leaves of C. blanchetianus against BAL W. viridescens and L. mesenteroides.